SUFFIX –SHI (-師) AND –FU (婦) AS PROFESSION MARKER SUFFIX IN JAPANESE LANGUAGE - Suryani Yayuk Saputri; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research discussed the meaning of words formed by the profession marking suffix -shi (-師) and -fu (-婦) in Japanese. This research used a qualitative descriptive, especially a method by using morphology and the meaning of kanji. The data were collected fromthe Japanese printed dictionary, the online Japanese dictionary on the weblio.jp website, the aedict online dictionary, and Japanese language corpus on the shonagon.ninjal.ac.id website. The obtained data then processed to examine their lexical meanings. The results of analysis showed that the suffixes – shi (- 師) and – fu (-婦) as professional indicators were frequentlyassociated with vocabulary of the kango word type. The words that were connected to these suffixes had a wide range of meanings. There were also other suffixes that refering to specific fields. The suffix –shi (-師) indicated a occupation that required exceptional abilities or qualifications in a specific subject, while the suffix –fu (-婦) had a work tendency that refered to only one gender, typically women. These rules determined which suffixes were attached to particular vocabulary in Japanese.Key Words: Suffix, Kanji, Profession Marker , Japanese Semantics